PENGEMBANGAN MODUL BERBASIS REALISTIK UNTUK MATERI HIMPUNAN DI KELAS VII SMPN 24 PADANG - Afreni, Tresia - (STKIP PGRI Sumbar, 2014)
The students are difficult to understand the set material on the textbook andstudent worksheet (LKS) of learning math. The textbook and LKS have notfacilitated the students to do an independent learning and had a realistic-based.The proposed solution of the problem is the development of a realistic-basedmodule for set material. The development aims to know the validity and practiceof realistic-based module for set material. The research uses 4-D model thatconsists of 4 stages, i.e. defining stage or need analysis, designing stage,developing stage, and disseminating stage. However, the research is onlyconducted until the third stage i.e. developing. The developing stage is conductedonly to see the validity and practice of the module. Data analysis is conducteddescriptively with the validity result i.e. very valid in which reaching the criteria4,55 and practice result i.e. very practice in which reaching the criteria 90%. Itmeans that the Modul Berbasis Realistik untuk Materi Himpunan di Kelas VIISMPN 24 Padang is valid and practical.